2023
DOI: 10.1038/s41467-023-43882-z
|View full text |Cite
|
Sign up to set email alerts
|

Topological electronic structure and spin texture of quasi-one-dimensional higher-order topological insulator Bi4Br4

Wenxuan Zhao,
Ming Yang,
Runzhe Xu
et al.

Abstract: The notion of topological insulators (TIs), characterized by an insulating bulk and conducting topological surface states, can be extended to higher-order topological insulators (HOTIs) hosting gapless modes localized at the boundaries of two or more dimensions lower than the insulating bulk. In this work, by performing high-resolution angle-resolved photoemission spectroscopy (ARPES) measurements with submicron spatial and spin resolution, we systematically investigate the electronic structure and spin textur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 54 publications
0
0
0
Order By: Relevance
“…Due to their favorable transport properties and high thermoelectric coefficient, they are regarded as outstanding thermoelectric materials for refrigeration and cooling [9,10]. With the study of topological insulators, it has been found that its properties have important applications in future information technology fields such as topological quantum computing, fault-tolerant quantum computing, thermoelectric devices and nonlinear optics [11,12]. Topological insulators, as a material with broad spectral absorption and nonlinear optical properties, have garnered significant attention from researchers [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their favorable transport properties and high thermoelectric coefficient, they are regarded as outstanding thermoelectric materials for refrigeration and cooling [9,10]. With the study of topological insulators, it has been found that its properties have important applications in future information technology fields such as topological quantum computing, fault-tolerant quantum computing, thermoelectric devices and nonlinear optics [11,12]. Topological insulators, as a material with broad spectral absorption and nonlinear optical properties, have garnered significant attention from researchers [13,14].…”
Section: Introductionmentioning
confidence: 99%